The predictive value of TyG index for ischemic stroke in patients undergoing maintenance hemodialysis - Wang, Yaqing; He, Xiaojie; Wang, Yuqing; Li, Xiaodong (Frontiers in Medicine, 2025)
ObjectivesTriglyceride-glucose (TyG) index is strongly correlated with insulin resistance (IR). A plethora of studies has established the role of TyG index in cerebrovascular diseases. However, the predictive value of TyG index for new-onset ischemic stroke (IS) in maintenance hemodialysis (MHD) patients remains unclear. This study aims to explore the correlation between TyG index and the occurrence of IS in MHD patients.MethodsThis study analyzed clinical data and cranial Computed Tomography results of patients undergoing MHD at Baoding First Central Hospital from January 2019 to January 2024. TyG index was calculated using fasting blood glucose and triglyceride levels. Univariate Logistic regression analysis was employed to identify factors associated with IS, incorporating variables with P < 0.05 into multivariate Logistic regression analysis, with results expressed as odds ratio (OR) and 95% confidence interval (95% CI). Receiver operating characteristic (ROC) curve analysis was used to evaluate the predictive value of TyG index for the occurrence of IS.ResultsTriglyceride-glucose index in the IS group was significantly higher than that in the non-IS group, with a statistically significant difference [9.32 (8.87, 9.92) vs 8.59 (8.06, 9.12), P < 0.001]. Variables with P < 0.05 from the univariate Logistic regression analysis, along with clinically relevant variables, were included in the multivariate Logistic regression analysis, indicating that an elevated TyG index is a factor associated with IS in hemodialysis patients (OR = 2.09, 95% CI 1.073–3.781, P < 0.001). ROC curve analysis revealed that the optimal cutoff value of TyG index for diagnosing new-onset IS in MHD patients was 9.2, with an area under the curve of 0.75 (95% CI 0.70–0.79, P < 0.001). Restricted cubic spline analysis demonstrated a non-linear relationship between TyG index and risk (non-linear p = 0.010).ConclusionTriglyceride-glucose index is significantly elevated in MHD patients with new-onset IS, serving as a potential risk factor for such events and offering valuable clinical diagnostic reference.